Women’s experiences of coping with the sexual side effects of antidepressant medication - O'Mullan, C.; Doherty, M.; Coates, R.; Tilley, Peter (TAYLOR & FRANCIS LTD, 2014)
A growing body of evidence has highlighted the sexual side effects of selective serotonin reuptake inhibitor (SSRI) medication. Whilst most of the research has focused on the prevalence and treatment of sexual difficulties, little is known about how patients cope with the SSRI-related sexual side effects. The objective of this study was to explore women’s experiences of coping with the sexual side effects of SSRI medication and interpretative phenomenological analysis was employed for an in-depth exploratory study of a sample of 10 women. Four broad themes emerged which are discussed under the following headings: searching, suffering in silence, trying to resolve and accepting what is. The themes provide an insight into the different strategies used by women to cope with the sexual side effects of SSRI medication and highlight the importance of contextualising these difficulties as part of an overall approach to improve the management and treatment of SSRI-related sexual side effects.